2000
DOI: 10.1038/35048610
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic binding of histone H1 to chromatin in living cells

Abstract: The linker histone H1 is believed to be involved in chromatin organization by stabilizing higher-order chromatin structure. Histone H1 is generally viewed as a repressor of transcription as it prevents the access of transcription factors and chromatin remodelling complexes to DNA. Determining the binding properties of histone H1 to chromatin in vivo is central to understanding how it exerts these functions. We have used photobleaching techniques to measure the dynamic binding of histone H1-GFP to unperturbed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

50
528
4
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(585 citation statements)
references
References 29 publications
50
528
4
3
Order By: Relevance
“…Recent results have indicated that the C-terminal domains of H1 proteins are primarily responsible for their DNA-binding properties (74), and it has been shown that synthetic peptides from the C-terminal domain of different H1 isoforms, including H1°, do not differ in their affinity for DNA (75). Recent experiments using H1-green fluorescent protein fusion proteins and photobleaching techniques have indicated a continuous and rapid exchange of H1 molecules in living cells (76,77). These results suggested that the binding behavior of linker histones in vivo is controlled mainly by factors other than subtype composition, such as linker histone phosphorylation and core histone acetylation (78), and that an eventual difference in linker histone affinity for chromatin in vitro depending solely on the difference in amino acid composition between H1°and the main H1 subtypes becomes too small to be resolved under our present experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results have indicated that the C-terminal domains of H1 proteins are primarily responsible for their DNA-binding properties (74), and it has been shown that synthetic peptides from the C-terminal domain of different H1 isoforms, including H1°, do not differ in their affinity for DNA (75). Recent experiments using H1-green fluorescent protein fusion proteins and photobleaching techniques have indicated a continuous and rapid exchange of H1 molecules in living cells (76,77). These results suggested that the binding behavior of linker histones in vivo is controlled mainly by factors other than subtype composition, such as linker histone phosphorylation and core histone acetylation (78), and that an eventual difference in linker histone affinity for chromatin in vitro depending solely on the difference in amino acid composition between H1°and the main H1 subtypes becomes too small to be resolved under our present experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, core histones are relatively immobile in the chromatin of cultured cells when compared with other chromatin components (such as linker histones, high mobility group (HMG) proteins and HP1) [33][34][35][36] . In the case of the core histone H3, only the variant H3.3 is loaded onto chromatin within the first day following nuclear transfer.…”
Section: Changes In Chromosomal Proteinsmentioning
confidence: 99%
“…Histone H1 is a fundamental part of chromatin, located at or near the entry/exit sites of DNA on the nucleosome and also binds to linker DNA (2,3). The binding of H1 proteins to chromatin is highly dynamic (4,5). Histone H1 stabilizes the nucleosome and is important in compaction of chromatin into higher order structures (6,7).…”
mentioning
confidence: 99%